Couple Card Learning Media in Improving Student Learning Outcomes in Class IV Science Subjects - Annaafi, Saifuloh; Setiawan, Deni (Universitas Pendidikan Ganesha, 2025)
The learning process in elementary schools often faces challenges regarding student involvement and understanding abstract concepts. Many students have difficulty understanding the material because the learning methods are still conventional and less interesting. As a result, student learning outcomes are low and do not reach the Minimum Completion Criteria (KKM). This study aims to test the effectiveness of couple card learning media compared to learning without interactive media on the learning outcomes of fourth-grade elementary school science students. This type of research is an experiment with a quasi-experimental research design in the form of a Non-Equivalent Control Group Design. The population of the study was 55 fourth-grade elementary school students. The sampling technique used purposive sampling. Elementary school Data collection techniques include test techniques (pre-test and post-test) and non-test techniques in the form of observation, interviews, and documentation. Initial data analysis techniques include normality and homogeneity tests and final data analysis with t-tests and N-Gain tests. From the results of the t-test, the sig value was obtained. In conclusion, learning using a couple of card media is effective. It has a higher average increase in learning outcomes than learning without interactive learning media in fourth-grade elementary school science students. The implications of this study indicate that learning strategies involving interactive and visual activities can significantly support students' conceptual understanding.